Utilization of 3D printed carbon gas diffusion layers in polymer electrolyte membrane fuel cells. (30th June 2022) - Niblett, Daniel; Guo, Zunmin; Holmes, Stuart; Niasar, Vahid; Prosser, Robert
Abstract: 3D printing and carbonisation is used to produce designed gas diffusion layer materials for polymer electrolyte membrane fuel cells (PEMFC). Using a desktop UV 3D printer, designed porous microstructures are printed with micro and macro-scale features. Successful improvement of the pyrolysis process maintains the structural accuracy during carbonisation, reducing the material to electrically conductive carbon. The size of the material allows for testing in a lab scale fuel cell with 1.5 × 1.5 cm electrode size, which shows lower but interesting electrochemical performance (power density of 205 mW cm −2 ). Challenges associated with integration of a 3D printed structure into a membrane electrode assembly are highlighted, including the low open circuit voltage caused by large amounts of membrane deformation and subsequent hydrogen crossover. This study shows that it is possible to design and manufacture a gas diffusion layer for fuel cells. Numerical simulation on the new GDL structure shows that advective-diffusive transport of oxygen in the 3D printed design is superior to conventional carbon paper. This study serves as the first attempt to implement 3D printed microstructures as GDL into PEMFC. Graphical abstract: Image 1 Highlights: A designed carbon gas diffusion layer is manufactured using 3D printing. Controlled pyrolysis is used to preserve microstructure. Challenges for 3D printed materials integrated into fuel cells are highlighted. Simulations show an 8% higher oxygen concentration at the catalyst layer.